Effects of Dietary Phospholipids on Growth Performance, Digestive Enzymes Activity and Intestinal Health of Largemouth Bass (Micropterus salmoides) Larvae - Wang, Shilin; Han, Zhihao; Turchini, Giovanni M.; Wang, Xiaoyuan; Fang, Zishuo; Chen, Naisong; Xie, Ruitao; Zhang, Haitao; Li, Songlin (Frontiers in Immunology, 2022)
While the beneficial roles of dietary phospholipids on health status and overall performances of fish larvae have been well demonstrated, the underlying mechanisms remain unclear. To address this gap, the present study was conducted to investigate the effects of dietary phospholipids on growth performance, intestinal development, immune response and microbiota of larval largemouth bass (Micropterus salmoides). Five isonitrogenous and isolipidic micro-diets were formulated to contain graded inclusion levels of phospholipids (1.69, 3.11, 5.23, 7.43 and 9.29%). Results showed that the supplementation of dietary phospholipids linearly improved the growth performance of largemouth bass larvae. The inclusion of dietary phospholipids increased the activity of digestive enzymes, such as lipase, trypsin and alkaline phosphatase, and promoted the expression of tight junction proteins including ZO-1, claudin-4 and claudin-5. Additionally, dietary phospholipids inclusion alleviated the accumulation of intestinal triacylglycerols, and further elevated the activity of lysozyme. Dietary phospholipids inhibited the transcription of some pro-inflammatory cytokines, including il-1β, and tnf-α, but promoted the expression of anti-inflammatory cytokines tgf-β, with these modifications being suggested to be mediated by the p38MAPK/Nf-κB pathway. The analysis of bacterial 16S rRNA V3-4 region indicated that the intestinal microbiota profile was significantly altered at the genus level with dietary phospholipids inclusion, including a decreased richness of pathogenic bacteria genera Klebsiella in larval intestine. In summary, it was showed that largemouth bass larvae have a specific requirement for dietary phospholipids, and this study provided novel insights on how dietary phospholipids supplementation contributes to improving the growth performance, digestive tract development and intestinal health.